The Determining Factors of the Financial Performance of Companies in the Construction Sector - Ana Maria Costea (Revista de Studii Financiare)
The paper outlines an investigation into the factors that determine the financial performance of companies in the construction sector. The data required for the analysis were collected for a specific sample of 30 companies in the construction field, with the reference period being the time interval between the years 2019-2022. The source used to create this sample was the annual financial statements of these companies published on the Bucharest Stock Exchange (BVB). The method by which the analysis was performed was the method of grouped least squares with fixed effects and random effects. This analysis is empirical with panel data.